Maine’s Clean Water Infrastructure: Transformative Power and Ongoing Needs - Kavanah, Brian (Maine Policy Review, 2023)
Maine’s clean water infrastructure, particularly municipal and quasi-municipal wastewater treatment facilities, was largely built after the establishment of the CWA when federal grant funding via the Environmental Protection Agency (EPA) Construction Grants Program was made available on a large scale. Clean water infrastructure is often out of sight and out of mind for most people, but the maintenance and upgrading of this essential infrastructure is critical to protect water quality and public health and to support economic growth.